Managing Business Integrity: Prevent, Detect, and Investigate White-collar Crime and Corruption - Heissner, Stefan (Springer, 2016)
This book deals with the highly complex but exciting subject of corporate fraud and corruption, which has since become the cops and robbers game of the 21st century: accounting fraud, embezzlement, bribery and many other forms of corruption and non-compliance cause turmoil between board members, supervisory board members and managers, while economic crime and corruption cause damages amounting to billions every year. When cases of misconduct and non-compliance become public knowledge, additional loss of reputation is the result, the consequences of which aren’t even quantifiable for the companies concerned.